Conservative treatment versus elective repair of umbilical hernia in patients with liver cirrhosis and ascites: results of a randomized controlled trial (CRUCIAL trial) - de Goede, B. (Langenbecks Arch Surg, 2020)
PURPOSE: To establish optimal management of patients with an umbilical hernia complicated by liver cirrhosis and ascites. METHODS: Patients with an umbilical hernia and liver cirrhosis and ascites were randomly assigned to receive either elective repair or conservative treatment. The primary endpoint was overall morbidity related to the umbilical hernia or its treatment after 24 months of follow-up. Secondary endpoints included the severity of these hernia-related complications, quality of life, and cumulative hernia recurrence rate. RESULTS: Thirty-four patients were included in the study. Sixteen patients were randomly assigned to elective repair and 18 to conservative treatment. After 24 months, 8 patients (50%) assigned to elective repair compared to 14 patients (77.8%) assigned to conservative treatment had a complication related to the umbilical hernia or its repair. A recurrent hernia was reported in 16.7% of patients who underwent repair. For the secondary endpoint, quality of life through the physical (PCS) and mental component score (MCS) showed no significant differences between groups at 12 months of follow-up (mean difference PCS 11.95, 95% CI − 0.87 to 24.77; MCS 10.04, 95% CI − 2.78 to 22.86). CONCLUSION: This trial could not show a relevant difference in overall morbidity after 24 months of follow-up in favor of elective umbilical hernia repair, because of the limited number of patients included. However, elective repair of umbilical hernia in patients with liver cirrhosis and ascites appears feasible, nudging its implementation into daily practice further, particularly for patients experiencing complaints. TRIAL REGISTRATION: Clinicaltrials.gov, NCT01421550, on 23 August 2011.